Figure 23 from: Cripps CL, Eberhardt U, Schütz N, Beker HJ, Evenson VS, Horak E (2019) The genus Hebeloma in the Rocky Mountain Alpine Zone. MycoKeys 46: 1-54. https://doi.org/10.3897/mycokeys.46.32823 - Cripps, Cathy L.; Eberhardt, Ursula; Schütz, Nicole; Beker, Henry J.; Evenson, Vera S.; Horak, Egon (Zenodo, 2019)
Figure 23 Micro-morphological features (basidiospores, basidia, cheilocystidia) of Hebeloma species found in the Rocky Mountain alpine zone. 1H.vaccinum (holotype, Herb. PC) 2H.aurantioumbrinum ZT12730 3H.subconcolor ZT 13776 4H.hiemale ZT9828 5H.avellaneum DBG-F-019533 6H.velutipes ZT6100 7H.alpinum CLC2875 8H.marginatulum ZT9002 9H.alpinicola ZT13763 10H.dunense ZT9001 11H.mesophaeum ZT8082 12H.excedens ZT7475 13H.oreophilum ZT12733 14H.hygrophilum CLC1462 15H.nigellum ZT6425 16H.spetsbergense micro in Fig. 22. Both two and four-spored basidiospores shown for 2, 5, 7, 8, 10, 12, 13, 15. Scale bar: 10 µm. All drawings by E. Horak.